PERANAN PEMIMPIN DALAM MENINGKATKAN DISIPLIN KERJA PADA PT BOSOWA BERLIAN MOTOR MAKASSAR - Harbani Harbani; Muslimin Muslimin; Muhammad Roif Dzamir (Jurusan Administrasi Niaga, Politeknik Negeri Ujung Pandang, 2022)
This study aims to determine: (1) how is the role of leaders in improving work discipline at the Branch Head of PT Bosowa Berlian Motor Makassar. (2) what is the factors hinder the leader's role in improving work discipline at the Branch Head of PT Bosowa Berlian Motor Makassar. The research method used is descriptive research type. The sampling technique used is a saturated sampling technique where the entire population is used as a sample of 75 samples. The data collection methods used are interviews, questionnaires and observation. Data analysis used is quantitative analysis supported by qualitative analysis and data processing using frequency distribution table. The results of this study indicated that the role of leaders in improving work discipline at the Branch Head of PT. Bosowa Berlian Motor Makassar can be said to be